Redescription of Iluocoetes Jenyns, 1842; proposal of a new genus, Argentinolycus, for Iluocoetes elongatus (Smitt, 1898), and description of Patagolycus melastomus gen. et sp. nov. (Teleostei, Zoarcidae) - Matallanas, Jesús; Corbella, Cecília (Zootaxa, 2012)
The osteological characters of the two nominal species of Iluocoetes, I. fimbriatus and I. elongatus are quite different. Thepresent definition of Iluocoetes based on osteological characters is not valid since it was based on characters found in I. elong-atus but not in I. fimbriatus, the type species of the genus. In this paper, Iluocoetes is redefined on the basis of osteologicalcharacters found in the holotype of Iluocoetes fimbriatus and other specimens of the species, and Iluocoetes elongatus is placedin another genus: Argentinolycus gen. nov. Besides, a new genus and species, Patagolycus melastomus, is described on thebasis of fourteen specimens, 94−437 mm TL, collected from SW Atlantic Ocean, at depths of 164−489 m. The similaritiesfound between Patagolycus melastomus sp. nov. and Iluocoetes fimbriatus in body colour as well as in many meristic and mor-phometric characters, represent a remarkable example of how challenging zoarcid taxonomy can be. The differences betweenthese two species are highlighted. A tree showing interrelationships among the Magellanic endemic lycodine genera is included.